12a+7-2a-3=

Simple and best practice solution for 12a+7-2a-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12a+7-2a-3= equation:


12a+7-2a-3=0

We simplify the equation to the form, which is simple to understand
12a+7-2a-3=0

We move all terms containing a to the left and all other terms to the right.
+12a-2a=0-7+3

We simplify left and right side of the equation.
+10a=-4

We divide both sides of the equation by 10 to get a.
a=-0.4

See similar equations:

| -15x^2-154x-25=0 | | 16v^3w^6+28v^5w^7y^2= | | 8t^2-4t^2= | | 10x^2=2x(h) | | Y-1=100 | | 16v^3w^6= | | 146-p^2=0 | | 8t^2+9t= | | h+1/4h+1/2h=x | | 3s-9s= | | -24x^-2y^5/9x^-8y^-7 | | 9d-3d= | | (9)(X)=18 | | X-6y+z=-12 | | 9-6x-3=4x+8 | | x+34=35 | | 1=8-2x | | 3x/2-9=5/3x+6 | | 3x/2-9=5/3+6 | | 9x+3y-5z=21 | | 6x+8=3x+9 | | 2x^-5y^7/14x^6y^3 | | -2(x+3)=4(x+11) | | x+13x+36= | | -10x+5=2x+6 | | -13x+7y=-3 | | x+2x+3x/2=6 | | 1+2i/-2+3i | | (6x-6/x+3)(x^2-3x-18/6x^2-6) | | (3-5)^2+(-24)/(3)(-2) | | 3/2(x+3)=4/5x-8 | | -5(a+2k)-8(-4+5k)= |

Equations solver categories